Optimizing Artificial Intelligence (AI) as a Catalyst for Digital Economic Transformation to Increase National Economic Growth - Sungkono,; I Dewa Ketut Kerta Widana, (Technium Social Sciences Journal, 2024)
This study aims to analyze a range of influential challenges to realize AI based economic transformation, thereby producing a comprehensive AI development strategy to maximize the benefits of AI with the minimum possible risk. Research data was obtained from interviews, observations, literature studies, and data triangulation. Based on the results of the study, it was found that the Indonesian Government needs to take several strategic steps in an effort to realize AI optimization to support economic transformation by strengthening the availability of equitable digital infrastructure to support AI implementation, increasing the availability of skilled human resources equivalent to AI technology capacity, providing conducive policy and regulatory support for AI investment and research, and optimizing the ecosystem that supports Innovation and technology startups for the development of AI-based products and services, in order to increase national economic growth.